‘Everything is translatable, nothing is translatable’: the migrant as translated/translator in Nadeem Aslam’s Maps for Lost Lovers - Daniela Vitolo (Angles)
A translation is always a process and never a simple one or a complete one. The task of the translator is to transpose meanings allowing distant worlds to make sense of each other but this always bears with itself a dimension of failure as nothing can be perfectly transposed from one language to another without losing or altering part of its meaning. If, as Salman Rushdie observes, from an etymological point of view to translate means to carry across, then the migrant is a ‘translated man’. The migrant’s translation implies physical, linguistic and cultural border-crossings that generate a process that shapes the migrant’s identity. This process is an act of sur-vival, both in the sense of living on the margins and in the sense of the migrant‘s dream for survival (Benjamin, Bhabha, Derrida, Rushdie). The paper proposes a reading of Nadeem Aslam’s novel Maps for Lost Lovers that analyses how it represents the relationship between translation and the Pakistani migrants’ processes of identity construction.